2020
DOI: 10.1080/26895293.2020.1817799
|View full text |Cite
|
Sign up to set email alerts
|

Review: phytochemistry and medicinal properties of Solanum torvum fruits

Abstract: Background: Most plants have medicinal properties, which they achieve from certain secondary metabolites. Phytochemicals are compounds produced by plants. They may affect health but are not-essential nutrients as our diet does not require them to sustain life in the same way as vitamins and minerals. Objectives: The study reports the phytochemistry and medicinal properties of Solanum torvum fruits. Methods: A search of database sites such as PUBMED, Google Scholar, and Web of Science as well as other sources o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…The combined methanolic extracts were evaporated at 35 ˚C (rotary evaporator HEILDOLPH Laborata 4003 Control, Schwabach, Germany) until 25 mL. These 25 mL of each phenolic extract Indonesian Food Science and Technology Journal IFSTJ : Vol : (6) No :1, December, 2022 (PP : [7][8][9][10][11][12][13][14][15][16][17][18] ISSN : 2615-367X…”
Section: Identification and Quantification Of Individual Phenolic Com...mentioning
confidence: 99%
See 1 more Smart Citation
“…The combined methanolic extracts were evaporated at 35 ˚C (rotary evaporator HEILDOLPH Laborata 4003 Control, Schwabach, Germany) until 25 mL. These 25 mL of each phenolic extract Indonesian Food Science and Technology Journal IFSTJ : Vol : (6) No :1, December, 2022 (PP : [7][8][9][10][11][12][13][14][15][16][17][18] ISSN : 2615-367X…”
Section: Identification and Quantification Of Individual Phenolic Com...mentioning
confidence: 99%
“…It is also cultivated as a small-scale vegetable in southern and eastern Asia, and is especially popular in Thailand [4]. In terms of traditional medicine, the berries of S. torvum have been widely investigated in many countries [2,6,7,8,9,10,11]. Extracts from these berries have generally been shown to be antioxidants, antimicrobials, anti-inflammatories, cardioprotectors, nephroprotectors, hepatoprotectors and cough suppressants.…”
Section: Introductionmentioning
confidence: 99%
“…S . torvum has alternate leaves which are broadly ovate with entire or lobed margins [ 10 ]. The globular shaped edible fruits grow in clusters and have a bitter taste when cooked whereas the stems have scattered hooked prickles [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…torvum have also yielded steroidal glycosides like 5α-pregn-16-en-3,20-dione-6α-ol-6-O-[α-L-rhamnopyranosyl-(1→3)-β-D-quinovopyranoside], 25(S)-26-O-β-D-glucopyranosyl-5α-furost-22(20)-en-3β,6α,26-triol-6-O-β-D-quinovopyranoside, 25(S)-26-O-β-D-glucopyranosyl-5α-furost-22(20)-en-3β,6α,26-triol-6-O-[α-L-rhamnopyranosyl-(1→3)-O-β-D-quinovopyranoside] and 5α-pregn-16-en-20-one-3β,6α-diol-6-O-[α-Lrhamnopyranosyl-(1→3)-β-D-quinovopyranoside] [ 19 ]; and phenolic compounds including methyl caffeate and isoflavonoid sulfate [ 20 ]. The fruits are reported to possess anti-ulcerogenic, anti-hypertensive, anti-inflammatory [ 10 ], antidiabetic [ 21 ], anticancer [ 22 ] and antibacterial activities [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phy-Blica-D has been reported to contain phytochemical compounds, including 6-galloylglucose, 1-O-galloylglycerol, fertaric acid, vanilpyruvic acid, (2S)-5,7,3′,4′-tetrahydroxyflavanone 6-C-glucoside, naringerin, agecorynin B, castavinol, chalconaringenin 2′-rhamnosyl-(1→4)-xyloside, beta-rhodomycin, sericoside, alliosterol 1-(4″-galactosylrhamnoside) 16-galactoside, licorice saponin A3, asparasaponin II, licorice saponin G2, betavulgaroside II, glycyrrhizic acid, and 6-gingerol [ 17 ]. Moreover, a literature review demonstrated that the phytochemical compounds of Phy-Blica-D herbal component are various, but the main chemicals are phenolic, flavonoid, alkaloids, glycosides, tannin, and triterpenoid, as shown in Table 1 [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%